Pengembangan Media Website Pemahaman Diri Untuk Meningkatkan Self-Efficacy Siswa - Indra Lacksana (Prosiding Temu Ilmiah Nasional Guru, 2022)
This research aims to produce a media generate a new innovation related to the media in educational psychology, which by using this blog media can help improve the self-efficacy owned by students. This means that by using the media effectively and efficiently, when the teacher counseling guidance cannot attendor late entry into the classroom, students can access their own and increase self-efficacy owned. Self-efficacy has a very important role associated with self-confidence in the potential associated with students' self-understanding. This research uses the simplified method of Borg and Gall into five stages by Puslitjaknov team, but this research is limited to small scale test. The results obtained from the use or empirical test that this product succeeded in improving self-efficacy of students proved by pretest and posttest by 36.5.